2013
DOI: 10.1037/a0029381
|View full text |Cite
|
Sign up to set email alerts
|

Letting go of the bad: Deficit in maintaining negative, but not positive, emotion in bipolar disorder.

Abstract: Bipolar disorder is a disorder of emotion regulation. Less is known, however, about the specific processes that foster the maintenance of such prolonged and intense emotions-particularly positive-over time in this disorder. We investigated group-related differences in the ability to maintain positive and negative emotion representations over time using a previously validated emotion working memory task (Mikels et al., 2005, 2008) among individuals with bipolar I disorder (BD; n = 29) compared with both major d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 48 publications
(84 reference statements)
1
29
0
1
Order By: Relevance
“…Euthymic patients were predominant in the samples (Malhi et al, 2007; Barrett et al, 2008; Dittman et al, 2008; Drapier et al, 2008; Thermenos et al, 2010; Levy et al, 2011; Mullin et al, 2012; Gruber et al, 2013; Lee et al, 2013; Miguélez-Pan et al, 2014; Russo et al, 2014; Bauer et al, 2015; Muhtadie and Johnson, 2015; Sabater et al, 2016), few studies evaluated depressions phases of BD (Deckersbach et al, 2008; Roiser et al, 2009; Bertocci et al, 2011) and only one compared the performance in manic and euthymic episodes in relation to health controls (Fleck et al, 2005). All studies have used between-groups comparison, and only article by Pomarol-Clotet et al (2014) also had a within-participants design and evaluated the same patients in three characteristics mood phases of BD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Euthymic patients were predominant in the samples (Malhi et al, 2007; Barrett et al, 2008; Dittman et al, 2008; Drapier et al, 2008; Thermenos et al, 2010; Levy et al, 2011; Mullin et al, 2012; Gruber et al, 2013; Lee et al, 2013; Miguélez-Pan et al, 2014; Russo et al, 2014; Bauer et al, 2015; Muhtadie and Johnson, 2015; Sabater et al, 2016), few studies evaluated depressions phases of BD (Deckersbach et al, 2008; Roiser et al, 2009; Bertocci et al, 2011) and only one compared the performance in manic and euthymic episodes in relation to health controls (Fleck et al, 2005). All studies have used between-groups comparison, and only article by Pomarol-Clotet et al (2014) also had a within-participants design and evaluated the same patients in three characteristics mood phases of BD.…”
Section: Resultsmentioning
confidence: 99%
“…The ranking for psychology, neuroscience, and medicine areas in the last 7 years were considered. Twenty-one studies were published in Q1 journals (Fleck et al, 2005; Malhi et al, 2007; Thompson et al, 2007; Barrett et al, 2008; Deckersbach et al, 2008; Drapier et al, 2008; Roiser et al, 2009; Liu et al, 2010; Thermenos et al, 2010; Bertocci et al, 2011; Levy et al, 2011; Mullin et al, 2012; Gruber et al, 2013; Lee et al, 2013; Pomarol-Clotet et al, 2014; Russo et al, 2014; Bauer et al, 2015; Gvirts et al, 2015; McCormack et al, 2015; Muhtadie and Johnson, 2015; Sabater et al, 2016), one in Q2 journal (Miguélez-Pan et al, 2014), and one in Q3 journal (Dittman et al, 2008). These quartiles also indicated that the majority of selected studies were published in higher impact factor journals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Number of lifetime manic episodes (range = 1–99 6 , M = 11.38, SD = 20.25) and depressive episodes (range = 0–99, M = 14.39, SD = 23.05) were assessed in the participants diagnosed with BD disorder using the NIMH-LCMr. All participants then completed a series of procedures not relevant to the present study (for other articles discussing this dataset, see Gilbert, Nolen-Hoeksema, & Gruber, 2013; Gruber, Kogan, Mennin, & Murray, in press; Gruber, Purcell, Perna, & Mikels, 2013; Kang & Gruber, 2013; Purcell, Phillips, & Gruber, 2013). At the end of the session, participants completed the extreme valuing of happiness and general goal pursuit scales using an online survey.…”
Section: Methodsmentioning
confidence: 99%
“…kontrasta), ujemanja s pozornostnimi filtri (Dolcos idr., 2008) ali čustvenosti (Dolcos, Kragel, Wang in McCarthy, 2006). Zmanjšana zmožnost inhibicije motečih informacij, še posebno če so le-te čustvene, je pomembna značilnost različnih čustvenih potez in motenj, kot so anksioznost (Fales, Becerril, Luking in Barch, 2010), depresija (Gruber, Purcell, Perna in Mikels, 2013;Joormann, Levens in Gotlib, 2011;Krause-Utz idr., 2012) in posttravmatska stresna motnja (Zhang idr., 2013).…”
unclassified